Effects of 3D perspective on head gaze estimation with a multiview autostereoscopic display. Issue 86 (February 2016) - Pan, Ye; Steed, Anthony
Abstract: Head gaze, or the orientation of the head, is a very important attentional cue in face to face conversation. Some subtleties of the gaze can be lost in common teleconferencing systems, because a single perspective warps spatial characteristics. A recent random hole display is a potentially interesting display for group conversation, as it allows multiple stereo viewers in arbitrary locations, without the restriction of conventional autostereoscopic displays on viewing positions. We represented a remote person as an avatar on a random hole display. We evaluated this system by measuring the ability of multiple observers with different horizontal and vertical viewing angles to accurately and simultaneously judge which targets the avatar is gazing at. We compared three perspective conditions: a conventional 2D view, a monoscopic perspective-correct view, and a stereoscopic perspective-correct views. In the latter two conditions, the random hole display shows three and six views simultaneously. Although the random hole display does not provide high quality view, because it has to distribute display pixels among multiple viewers, the different views are easily distinguished. Results suggest the combined presence of perspective-correct and stereoscopic cues significantly improved the effectiveness with which observers were able to assess the avatar׳s head gaze direction. This motivates the need for stereo in future multiview displays. Abstract : Highlights: Represented a remote person as an avatar on a random hole display (RHD). This RHD provides multiple users with perspective-correct stereo views from arbitrary positions. Evaluated a RHD for improving the head gaze perception for group teleconferencing. A perspective-corrected rendering improved viewers׳ ability in head gaze perception. Adding stereoscopic cues provided an additional improvement in head gaze perception.